Synthesis of 15N-labelled nitro compounds with a 2,4,6-trinitrophenyl group - Jalový, Zdeněk; Ryšavý, Jan; Vodochodský, Ondřej; Jančík, Milan; Labaj, Miroslav (Univerzita Pardubice, 2020)
The synthesis of 2,4,6-(15N3)-trinitrophenol (picric acid-(15NO2)3), 1-Chloro-2,4,6-(15NO2)3-trinitrobenzene (picrylchloride-(15NO2)3) and various 15N labelled compounds with a 2,4,6-trinitrophenyl (picryl) moiety is described. 15N labelled isotopomers of 2,4,6-trinitroaniline (picramide), N-methyl-N-nitro-2,4,6-trinitroaniline (tetryl) and 3,5-dinitro-N,N´-bis-(2,4,6-trinitrophenyl)pyridine-2,6-diamine (PYX), labelled at different nitrogen atoms were prepared. Potassium (15N)nitrate or sodium (15N)nitrate were used as the source for the (15N)nitro groups. The infrared and Raman spectra of the materials are evaluated, especially the position and shift of (15N)nitro groups. The characteristic infrared and Raman frequencies connected with nitro groups are shifted in the corresponding 15N-labelled materials.
Syntéza 15N-lznačených nitrosloučenin s 2,4,6-trinitrofenylskupinou
Keywords: nitroaromatics; 15N labelled; FTIR; Raman; nitroaromáty; 15N značené; FTIR; Raman